2021
DOI: 10.1177/17423953211064989
|View full text |Cite
|
Sign up to set email alerts
|

Using Communities of Practice Theory to Understand the Crisis of Identity in Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME)

Abstract: Objective To explore the crisis of identity in Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME) through the lens of Communities of Practice. Methods A closed Facebook group was created to gather qualitative data from participants diagnosed with CFS/ME (n = 22). Data were analysed using a theoretical thematic analysis. Results The current research revealed the reality of enabling and disabling communities in the lived experience of CFS/ME and the role of participation in developing empowered identiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…The insider perspective allows access to a familiar lived experience which facilitates the research process in ways an outsider perspective could not. 28 Flexibility of the method and rapid building of rapport during email exchanges may have contributed toward participant retention; the rapport between researcher and participant, both as insiders, often reflects a shared empathy 25 and can engender trust.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insider perspective allows access to a familiar lived experience which facilitates the research process in ways an outsider perspective could not. 28 Flexibility of the method and rapid building of rapport during email exchanges may have contributed toward participant retention; the rapport between researcher and participant, both as insiders, often reflects a shared empathy 25 and can engender trust.…”
Section: Discussionmentioning
confidence: 99%
“…There are large online social media communities where people with TTM can join together to talk about their experiences; these online communities provide a powerful ‘virtual’ connection to people throughout the world who have a shared diagnosis. 25 Qualitative purposive sampling involves selecting individuals who are knowledgeable about or have experience with a phenomenon of interest. 26 Further, it allows voices from stigmatized populations to be heard, by reflecting experiences that capture the emic view.…”
Section: Methodsmentioning
confidence: 99%
“…There is a concept that has been little explored in the trajectories: reification -transformation of bad events into material strategies (treatment strategies after a diagnosis or "doing something with what has been given to me" due to the label of chronic condition), generating new reified identities. At this point, there is an exception: stigmatized identities should not be reified, as this hinders the experience of legitimate participation and engagement 36 .…”
Section: Delimitation Of a Healthcare Community Of Practice: Reified ...mentioning
confidence: 99%
“…This was found in a research on the chronic fatigue syndrome, which revealed professionals' skepticism concerning symptoms and marginalization inside the community itself, culminating in an illegitimate, disabling and psychosomatic trajectory. Thus, when this reification occurs, participation was useless 36 .…”
Section: Delimitation Of a Healthcare Community Of Practice: Reified ...mentioning
confidence: 99%
“…Há um conceito pouco explorado nas trajetórias: a reificação -transformação de eventos ruins em estratégias materiais (estratégias de tratamento após um diagnóstico ou "fazer algo com o que me foi dado", devido ao rótulo de condição crônica), gerando novas identidades reificadas. Nesse ponto, há uma ressalva: identidades estigmatizadas não devem ser reificadas, pois uma experiência de participação legítima e de engajamento é dificultada com isso 36 .…”
Section: Delimitação De Uma Comunidade De Prática Na Saúde: Identidad...unclassified